1994
DOI: 10.1002/mrd.1080390217
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia inhibitory factor and the regulation of pre‐implantation development of the mammalian embryo

Abstract: This paper reviews the evidence that certain growth factors, particularly leukaemia inhibitory factor (LIF), play a crucial role in regulating the development of the pre-implantation mammalian embryo. LIF was originally implicated in regulating the early development of the mouse embryo because it inhibited the differentiation of embryonic stem (ES) cells, pluripotential cells derived from the inner cell mass of the blastocyst. Subsequent studies on its role in vivo revealed, surprisingly, that it is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 46 publications
1
50
0
4
Order By: Relevance
“…Whether this is due to the action of LIF directly on the blastocyst or that of a paracrine activation of gene expression in the surrounding maternal tissue has not yet been proven. However, consistent with the latter proposal, LIF 2/2 females mated with vasectomized males were unable to undergo an induced decidual reaction, where uterine stromal cells proliferate and differentiate to produce a decidual mass (Stewart, 1994). Because Stat3 is activated in response to LIF and because we have demonstrated the presence of active Stat3 in the decidua, it is likely that Stat3 plays an important role during decidualization and for the provision of a suitable maternal environment for the development of the early postimplantation embryo.…”
Section: Discussionsupporting
confidence: 66%
“…Whether this is due to the action of LIF directly on the blastocyst or that of a paracrine activation of gene expression in the surrounding maternal tissue has not yet been proven. However, consistent with the latter proposal, LIF 2/2 females mated with vasectomized males were unable to undergo an induced decidual reaction, where uterine stromal cells proliferate and differentiate to produce a decidual mass (Stewart, 1994). Because Stat3 is activated in response to LIF and because we have demonstrated the presence of active Stat3 in the decidua, it is likely that Stat3 plays an important role during decidualization and for the provision of a suitable maternal environment for the development of the early postimplantation embryo.…”
Section: Discussionsupporting
confidence: 66%
“…Other investigators, however, have not observed a beneficial effect of PDGF on development of mouse embryos (Colver et al, 1991 ) or cow embryos (Flood et al, 1993). The LIF, a glycoprotein expressed on cultured mouse blastocysts (Murray et al, 1990) and in the uterine endometrial glands of mice by the fourth day of pregnancy, is maternally controlled and is essential for implantation (reviewed by Stewart, 1994). The addition of human LIF (hLIF) to the culture medium increased the number of eight-cell stage mouse embryos which hatched and increased the size of blastocyst outgrowths in vitro (Robertson et al, 1991;Lavranos et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, today there are already some biomarkers confirmed in separate studies which are pivotial during implantation process. For example, the most potential endometrial marker identified is leukemia inhibitory factor (LIF) and its importance has been proven in animal and human studies (Stewart et al, 1994;Arici et al, 1995;Steck et al, 2004). Unfortunately, the development of recombinant human LIF (r-fLIF) has not met the expectations of increasing implantation rates in infertile women (Brinsden et al, 2009).…”
Section: Endometrial Gene Expression During the Time Of Embryo Implanmentioning
confidence: 99%